PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DALAM PEMENUHAN HAK PEKERJA YANG DIPUTUS HUBUNGAN KERJA - Nur Febya Adhawiyah; Imam Budi Santoso (The Juris, 2022)
Termination of employment is a common occurrence in the world of work, especially in the industrial sphere where there is a great need for workers, especially laborers or freelancers. Not infrequently of those who have been laid off due to several factors, especially since the Covid-19 virus in Indonesia, it is not only one or two companies that have reduced employees, but many companies have reduced employees. From here, of course, not all of them get the right and proper rights, there are some of them that do not receive their rights as they should.